Efecto probiótico intrauterino de Lactobacillus gasseri en hembras bovinas posparto con endometritis subclínica - Martínez Cepeda, Galo Ernesto (2023)
The study was to isolate, identify and characterize an autochthonous strain of \nLactobacillus gasseri from the tropical zone of Ecuador and to analyze the \nbiotherapeutic effects on the endometrium of postpartum bovine females with \nsubclinical endometritis; performing an experimental design composed of 3 groups. For this process, 418 animals were sampled for the isolation of 10 strains of Lactobacillus gasseri to which the following characterization tests were applied: growth in hostile conditions, determination of hydrophobicity, hemagglutination, hemolytic activity, aggregation, production of hydrogen peroxide , coaggregation with pathogens, growth \ninhibition, susceptibility to microbial agents and cytotoxicity. Once the best strain of lactic acid bacteria (LAB) had been characterized and selected, bovine females were inoculated with a live culture of the strain at 30 days postpartum, and its effects were checked 30 days later, using biopsy, cytology and uterine ultrasound techniques; \nidentifying the changes at the cytological and histological level in the cows that presented subclinical endometritis. The results obtained from the characterization process through a scoring system and a component analysis of the 10 isolated strains were 2 strains with probiotic characteristics, of which the 3rd strain with the highest \nscore was used. Within the experimental design that consisted of a negative control, positive control and treatment group, the biotherapeutic effect of BAL was demonstrated (p<0.001), favoring the process of uterine involution (p<0.001) and improving the conception rate at the first service of animals that had presented the pathology. In conclusion, it was shown that Lactobacillus gasseri LgEc003 is an \nexcellent candidate for the development of a biotherapeutic in postpartum bovine females, improving reproductive parameters and uterine health